(untitled) - O. Lee Reed (Boston, 2005)
In 1963, the first edition "Legal and Regulatory Environment of Business", led by Bob Corley, started a new course emphasizing the legal environment in which business is conducted. By focusing on the public nature of how government regulates business activities, rather than simply how businesses privately make transactions, a movement away from traditional Business Law began. Through its previous 12 editions, "Legal and Regulatory Environment of Business" by Reed, Shedd, Morehead and Corley has been the leader in setting the standard for materials covered in an introduction to the legal and regulatory environment of business
Keywords: Trade regulation; Commercial law; Industrial laws and legislation